PELATIHAN MANDIRI FINANSIAL UMKM PABRIK TEMPE ANTO WONOSARI 3 AEK KANOPAN - Raja Saul Marto Hendry, Daslan Simanjuntak (JURNAL BIMA, 2026)
Low financial literacy and inadequate bookkeeping are serious problems for the Anto Wonosari 3 Aek Kanopan Tempe Factory in North Labuhanbatu Regency. To address this challenge, a community service program was launched through a survey, training, and mentoring approach. The material presented focused on basic financial practices, such as separating personal and business assets, recording every transaction, calculating COGS, and preparing profit and loss reports. Participants' understanding has shown a dramatic increase, as evidenced by a 41% jump in post-test scores. Operationally, business owners have begun to discipline themselves in recording finances directly and using factual data for pricing. This underscores that mastering financial literacy is not only a matter of survival for MSMEs, but also a catalyst for the economic progress of households and the surrounding community.